The Effect of Audit Committee on Integrated Reporting Disclosure with Gender Diversity as Moderation - Fartimah, Siti; Suprianto, Edy (Jurnal Kajian Ruang, 2025)
Abstract. This study aims to determine the relationship of the audit committee on the disclosure of integrated reporting and whether gender diversity is able to moderate the effect of the audit committee relationship on the disclosure of integrated reporting. Integrated Reporting is measured based on the number of elements disclosed, the audit committee is measured based on the number of meetings held, while gender diversity is measured based on the presence of women on the board. The sample in this study is a banking company listed on the Indonesia Stock Exchange for the period 2020 - 2023. The results showed that the Audit Committee had no effect on Integrated Reporting disclosure while gender diversity was able to moderate the effect of the audit committee on Integrated Reporting disclosure.Keyword : Integrated Reporting Disclosure, Audit Committee, Gender Diversity